My home—my castle? Self-reported anxiety varies in relation to the subjective evaluation of home environment - Weber, Sandra; Mascherek, Anna; Augustin, Jobst; Cheng, Bastian; Thomalla, Götz; Hoven, Hanno; Harth, Volker; Augustin, Matthias; Gallinat, Jürgen; Kühn, Simone (Frontiers in Psychology, 2024)
Abstract Introduction. Although people spend most of the day in their home environment, the focus of research in environmental psychology to date has been on factors outside the home. However, it stands to reason that indoor quality likewise has an impact on psychological well-being. Therefore, the present study addresses the question of whether the subjective evaluation of home environmental parameters are related to self-reported anxiety and whether they can additionally explain variance beyond the usual sociodemographic and general lifestyle variables. Method. Data from the Hamburg City Health Study (first 10,000 participants) was analyzed. A subsample of N = 8,886 with available GAD-7 anxiety data was selected, and hierarchical regression models were computed, with demographic data entered first, followed by variables concerning lifestyle/ habits and finally variables of the subjective evaluation of home environment. Results. Using the integrated model, we were able to explain about 13% of the variance in self-reported anxiety scores. This included both the demographic, lifestyle, and subjective evaluation of home environment variables. Protection from disturbing night lights, a greater sense of security, less disturbing noises, brighter accommodations, and a satisfactory window view explained almost 6% of the variance and was significantly associated with lower anxiety scores. Conclusion. The home as a place of refuge plays an increasingly important role as home office hours rise. It is therefore crucial to identify domestic factors contributing to people's mental well-being. The subjective evaluation of one’s home environment has proven influential over and above modifiable lifestyle variables.